Pharmacokinetics of menbutone after intravenous and intramuscular administration to sheep - Diez, Raquel; Diez, M. Jose; Garcia, Juan J.; Rodriguez, Jose M.; Lopez, Cristina; Fernandez, Nelida; Sierra, Matilde; Sahagun, Ana M. (Frontiers in Veterinary Science, 2022)
Menbutone is a drug currently approved in several European Union (EU) countries to treat digestive disorders in different animal species. The objective of this study was to establish the pharmacokinetic parameters resulting from intravenous (IV) and intramuscular (IM) administration of this drug in sheep. Menbutone was administered to 12 animals at the dose of 10 mg/kg for both IV and IM routes. Plasma samples were collected up to 24 h (15 points, IV route; 14 points, IM route). Concentrations were determined using high-performance liquid chromatography with photodiode-array (PDA) detection, following a method validated according to the EMEA/CHMP/EWP/192217/2009 guideline. Pharmacokinetic data were analyzed by non-compartmental methods. After IV administration, a total clearance (Cl) of 63.6 ± 13.6 mL/h/kg, a volume of distribution at steady-state (Vss) of 259.6 ± 52.7 mL/kg, and an elimination half-life (t½λ) of 6.08 ± 2.48 h were calculated. After IM administration, menbutone peak plasma concentration (Cmax) was 18.8 ± 1.9 µg/mL, the time to reach Cmax (tmax) 3.75 ± 0.45 h, the mean absorption time (MAT) 3.31 ± 1.36 h, and the fraction of dose absorbed (F) 103.1 ± 23.0 %. The results obtained indicate that menbutone absorption after IM administration is quick and complete.